Functional Stylistics in the TEXTUAL respect: Message Organization Patterns for Literary Discourse. (10th December 2015) - Peng, Xuanwei
Abstract : Systemic Functional Linguistics has experienced over 40 years of application to literary discourse analysis and gained considerable achievements, with particular reference to the ideational and interpersonal areas. Contrary to that situation is the textual area, which, except for cohesion, is much less explored in thematization and information. This paper aims to fill this gap. Taking the short narrative text Gehenna I investigate thematic and information creating patterns for their aesthetic effects. There exist types of unfolding routines in literary texts that are oriented towards stylistic goals. The observations manifest once again the power of SFL in its appliability.